2016
DOI: 10.1590/s1678-9946201658002
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance Patterns of Urinary Tract Infections in a Northeastern Brazilian Capital

Abstract: Urinary tract infection is a common problem worldwide. Its clinical characteristics and susceptibility rates of bacteria are important in determining the treatment of choice and its duration. This study assessed the frequency and susceptibility to antimicrobials of uropathogens isolated from community-acquired urinary tract infections in the city of Natal, Rio Grande do Norte State capital, northeastern Brazil, from 2007 to 2010. A total of 1,082 positive samples were evaluated; E. coli was the most prevalent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
31
1
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 19 publications
8
31
1
11
Order By: Relevance
“…The results also show that different organisms showed different proportions of antibiotic resistance to the different antibiotics, relative to the total number of each organism isolated and tested for antibiotic resistance. The high level of resistance shown to some of these antibiotics, especially ampicillin, agrees with other findings that have also reported elevated level of resistance to ampicillin and the 3 rd generation cephalosporins [28,29]. Another study by Leski et al, (2016) [6] reported widespread resistance to sulphonamides, chloramphenicol and gentamicin among Gram-negative bacteria isolated from patients with UTIs, although resistance to ampicilin was moderate.…”
Section: Discussionsupporting
confidence: 87%
“…The results also show that different organisms showed different proportions of antibiotic resistance to the different antibiotics, relative to the total number of each organism isolated and tested for antibiotic resistance. The high level of resistance shown to some of these antibiotics, especially ampicillin, agrees with other findings that have also reported elevated level of resistance to ampicillin and the 3 rd generation cephalosporins [28,29]. Another study by Leski et al, (2016) [6] reported widespread resistance to sulphonamides, chloramphenicol and gentamicin among Gram-negative bacteria isolated from patients with UTIs, although resistance to ampicilin was moderate.…”
Section: Discussionsupporting
confidence: 87%
“…Infecção do trato urinário é uma das doenças mais comumente encontrada e causada principalmente por enteropatógenos e acomete indivíduos de todas as faixas etárias, em todo o mundo. 5 Dentre os microrganismos identificados, a E. coli (75,6%) foi o principal patógeno responsável por ITU de origem comunitária e sua prevalência foi significativamente maior entre as mulheres (79,0%) (p<0,05) como encontrado em outro. Entretanto, essa prevalência pode variar entre diferentes regiões geográficas.…”
Section: Discussionunclassified
“…3,4 Desde o advento da introdução da penicilina no arsenal terapêutico de uso humano, assiste-se o crescente aumento da prevalência de microrganismos resistentes tanto nas ITU de origem hospitalar quanto comunitária. 5 Para o tratamento empírico deve-se considerar o agente etológico mais provável, o uso prévio de antimicrobianos, a disponibilidade do antimicrobiano, a farmacocinética do medicamento, e o padrão local de resistência. Variações no perfil de resistência ocorrem entre diferentes regiões geográficas, mesmo dentro do mesmo país.…”
Section: Introductionunclassified
“…They settled conflicts through discussion. They developed an excel sheet to collate the following information: (1) author name, (2) year, (3) study design, (4) risk of bias, (5) study setting (community or hospital), (6) age group (adults and children or adults only), (7) country, (8) economic standard, and (9) region (Africa, Asia, Middle East, Europe, and North and South American). Specific data included the duration of each study in months, the number of E. coli positive urine samples, and the number of ciprofloxacin-resistant samples.…”
Section: Data Extractionmentioning
confidence: 99%
“…Pseudomonas aeruginosa, staphylococcus spp., and Proteus spp. are other causative organisms (5). UTIs occur in either nosocomial/community-acquired (CA) or Hospital-acquired (HA) forms.…”
Section: Introductionmentioning
confidence: 99%